Ausência de arteriosclerose na porção intramiocárdica das artérias coronárias: Um mistério a ser resolvido? - Ramalli Jr, Edvaldo Luiz (2011)
Several studies show that portions of intramyocardial coronary arteries are spared of arteriosclerosis, involving morphological, embryological, biochemical and pathophysiological aspects. Endothelial function is significantly affected in the segment of transition, as estimated by the vasoactive response to Ach. These findings suggest that myocardial bridge can provide protection against arteriosclerosis by counteracting the negative effects of endothelial dysfunction. The intramyocardial portion's protection phenomenon deserves further scientific research on all research fronts. Improved morphological, biomechanical and especially physiological and embryological knowledge may be the key to a future window of opportunity for chronic arterial disease therapy and prevention. In addition, this review discusses possible therapeutic approaches for symptomatic coronary ischemia caused by myocardial bridges.